Towards Automated Detection and Localization of Red Deer Cervus elaphus Using Passive Acoustic Sensors during the Rut - Avots, Egils; Vecvanags, Alekss; Filipovs, Jevgenijs; Brauns, Agris; Skudrins, Gundars; Done, Gundega; Ozolins, Janis; Anbarjafari, Gholamreza; Jakovels, Dainis (MDPI, 2022)
Passive acoustic sensors have the potential to become a valuable complementary component in red deer Cervus elaphus monitoring providing deeper insight into the behavior of stags during the rutting period. Automation of data acquisition and processing is crucial for adaptation and wider uptake of acoustic monitoring. Therefore, an automated data processing workflow concept for red deer call detection and localization was proposed and demonstrated. The unique dataset of red deer calls during the rut in September 2021 was collected with four GPS time-synchronized microphones. Five supervised machine learning algorithms were tested and compared for the detection of red deer rutting calls where the support-vector-machine-based approach demonstrated the best performance of -96.46% detection accuracy. For sound source location, a hyperbolic localization approach was applied. A novel approach based on cross-correlation and spectral feature similarity was proposed for sound delay assessment in multiple microphones resulting in the median localization error of 16 m, thus providing a solution for automated sound source localization-the main challenge in the automation of the data processing workflow. The automated approach outperformed manual sound delay assessment by a human expert where the median localization error was 43 m. Artificial sound records with a known location in the pilot territory were used for localization performance testing.
Keywords: wildlife acoustics; red deer; Song Meter SM4TS; sound detection; sound localization; automated data processing; support vector machine; cross-correlation; spectral feature similarity; LOCATION; PRIMATES; Environmental Sciences & Ecology; Geology; Remote Sensing; Imaging Science & Photographic Technology